Computational Analysis of Bioethanol Production from Arenga Pinnata Sap using Rice Husk Biomass Heating: Statistical Modeling of Fermentation Time Effects on Alcohol Yield - Saroinsong, Tineke; Mekel, Alfred Noufie; Motulo, Firmansyah Reskal (Asosiasi Dosen Muda Indonesia, 2025)
This study presents a comprehensive computational analysis of sustainable bioethanol production from Arenga pinnata sap using rice husk biomass as a renewable heating source. The research investigated fermentation time effects on alcohol yield through systematic experimentation and Python-based statistical modeling across four conditions: fresh sap, 1-day, 3-day, and 18-day fermentation periods. Distillation processes utilized 8.5 kg rice husk biomass at 80°C for 1.42 hours, producing 600 ml bioethanol per batch. Statistical analysis revealed a highly significant inverse correlation (r = -0.965, p < 0.05) between fermentation duration and alcohol content. Fresh palm sap yielded optimal alcohol concentration of 39.67 ± 7.76%, while 18-day fermentation reduced yield to 2.50 ± 2.50%, representing 93.7% decrease. The exponential decay model (R² = 0.984) demonstrated superior predictive accuracy compared to linear regression. The integrated system achieved 70.6 ml bioethanol per kg rice husk with positive energy balance (1.23 MJ output per MJ input), confirming commercial viability for rural renewable energy applications. This computational framework establishes optimal processing parameters for agricultural waste-powered biofuel systems, supporting circular economy principles and rural energy independence through effective biomass utilization in tropical regions.